Pengaruh Micro Influencer, Endorsement, dan Digital Marketing terhadap Purchase Decision pada Barley Store Kediri - Ragil Satria Pratama; Ustadus Sholihin; Nurali Agus Najibul Zamzam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This quantitative study aims to examine the influence of micro influencer (X1), endorsement (X2), and digital marketing (X3) on purchase decision (Y) at Barley Store Kediri. Data were collected through questionnaires, literature reviews, and documentation, involving 120 respondents. The analysis methods used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, t-test, F-test, and Coefficient of Determination. The regression equation obtained is: Y = 3.946 + 0.329X1 + 0.217X2 + 0.264X3 + e. The t-test results show that micro influencer (t = 2.715, sig. = 0.008), endorsement (t = 2.125, sig. = 0.036), and digital marketing (t = 2.489, sig. = 0.014) each have a significant partial effect on purchase decision. The F-test result (F = 19.182, sig. = 0.000) indicates a significant simultaneous effect of all three variables on purchase decision. Thus, micro influencer, endorsement, and digital marketing all significantly influence consumers’ purchasing decisions, both partially and simultaneously.